Science communication by scientists and influencers on social media - Imamatul Silfia; Irwansyah Irwansyah (Manajemen Komunikasi, 2022)
This study analyzes the shift in the science communication landscape, which is starting to be influenced by the presence of influencers on social media. Influencers who influence to construct audience opinions allow the birth of different interpretations of scientific information among the audience, especially the lay audience. These can be seen in the discussion about wildlife care tweeted by veterinarian Nur Purba Priambada who criticized influencer Alshad Ahmad. The reaction to Purbo's tweet shows that not all audiences agree with the scientific information shared by Purbo, even though Purbo has a scientific background. On the other side, some audiences support the influencer Alshad Ahmad who keeps the wildlife on his own. This study uses the netnographic method. This study aims to examines how science communication that takes place on social media affects audience reactions to scientific information shared by scientists and influencers, in this case, Purbo and Alshad Ahmad. The study result shows that the audience does not necessarily believe the information shared by people with scientific backgrounds in a scientific discussion on social media. Although some audiences believe the scientists' scientific information, other audiences trust the influencer more. This finding can be a consideration for scientists to develop an effective communication style on social media regarding scientific information to audiences, especially lay audiences.